Genetic Change of Pharella acutidens Influenced by Pb and Cd Metals in Rupat Strait Waters - Tri Vani Bernadetha Ginting; Syafruddin Nasution; Irwan Effendi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2021)
Rupat Strait related to the Strait of Malacca is a national and international shipping lane and makes the region affected by anthropogenic activities that result in a decrease in the quality of the waters such as the increasing amount of heavy metal content. The most easily contaminated organism of heavy metals is bivalves due to and its low mobility, bivalves being filter feeders, and the ability to accumulate contaminants,. The purpose of this study was to look at genetic changes in bivalves (P.acutidens) contaminated by heavy metals. The study was conducted from February to March 2021. Bivalve sample was collected from the waters of Rupat Strait and sample analysis was conducted in the Marine Biology Laboratory and Genetics Laboratory of Riau University. Bivalve DNA is isolated with Geneaid Tissue Genomic DNA Mini Kit. DNA isolation results were then carried out PCR process and sequencing process was carried out in PT. Genetika Science Indonesia. The results of study show that sequencing results obtained by samples derived from Selinsing have the most changes in the composition of nitrogen bases compared to samples from the other two stations